PEMBAURAN BUDAYA DI DESA RANTAU SAKTI KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Siti Nurlaila; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study is to research how the intercourse of culture that existed in the Rantau Sakti village Tambusai Utara District and Rokan Hulu Regent intertribal nasions of Java, Medan Java, Batak, Minang, and Melayu. There’s a launching factors and hindrance factors too in culture intercourse. The data tekhnic collection with the koesioner, interview, and documentation. And the analisys of data is descriptive where the data presented in the form of a diagrams, percentages, pictures, and explanations. The research results show that The lives of the multicultural that could lead to the occurrence of intercourse of culture through assimilation, acculturation, and amalgamation. The intercourse of culture through three aspects of it can run well there’s happened in Rantau Sakti village on seven principles like language, system of knowledge , a social organization , celebration life and technologi, means of subsistence, religion, and art . There is also intercourse of culture with amalgamation culture that leads to assimilation and acculturation. It’s launching factor are the attitude of tolerance and open, in common religion, and the same occasion in the economic field. While the hindrance factor are differences of religion and stereotype (ethnic prejudice). Those two factors each happened to the process of changing culture with assimilation, acculturation, and amalgamation That leads to a positive thing.Keyword: The Culture Intercourse, Inter-ethnic.